A RELEVANCE BETWEEN MATLA’ WILAYATUL ḤUKMI TOWARDS THE IMPLEMENTATION RESULT OF RUKYATUL HILAL AND WUJUDUL HILAL - Restu Trisna Wardani; Ahmad Izzuddin (Al-Hilal: Journal of Islamic Astronomy, 2020)
In Indonesia there are still often differences in the determination of the beginning of the Hijri month (Kamariah). This is due to the difference between the concept of rukyatul hilal and wujudul hilal is use by the largest religious organization in Indonesia. It is know from several literature sources that Nahdlatul Ulama applies the concept of rukyatul hilal, while Muhammadiyah applies the concept of wujudul hilal. Both have advantages and disadvantages of each. In addition, both of them also apply the concept of wilayatul ḥukmi enforces the initial determination of the Hijri month for a particular jurisdiction, it is valid for a country or government. Following up on this matter, this study wanted to describe the relevance between the concepts of rukyatul hilal and wujudul hilal in the implementation of the wilayatul ḥukmi concept. Problems related to wilayatul ḥukmi will occur if in a hilal area it cannot be seen when the rukyatul hilal process or in a new hilal area has not been realized when applying the wujudul hilal concept. Moving on from the above problems, the question arises as to how the concept of wilayatul ḥukmi is able to accommodate these two concepts, where the jurisdiction included in the reality does not meet the criteria to enter the beginning of the new month. On the other hand, this study also wants to uncover the advantages and disadvantages between the concept of rukyatul hilal and wujudul hilal in the current era, with the hope of being able to provide positive criticism in building common ground for the benefit of the people.  Di Indonesia masih sering terjadi perbedaan dalam penetapan awal bulan Hijriah (Kamariah). Hal ini karena adanya pebedaan antara konsep rukyatul hilal dan wujudul hilal yang digunakan oleh organisasi keagamaan terbesar di Indonesia. Diketahui dari beberapa sumber pustaka bahwa Nahdlatul Ulama menerapkan konsep rukyatul hilal, sedangkan Muhammadiyah menerapkan konsep wujudul hilal. Keduanya mempunyai kelebihan dan kekurangan masing-masing. Selain itu, keduanya juga menerapkan konsep wilayatul ḥukmi yang memberlakukan penetapan awal bulan Hijriah untuk satu wilayah hukum tertentu, yakni untuk suatu negara atau pemerintahan. Menindaklanjuti hal tersebut, penelitian ini ingin mendeskripsikan relevansi antara konsep rukyatul hilal dan wujudul hilal dalam implementasi konsep wilayatul ḥukmi. Permasalahan terkait wilayatul ḥukmi akan terjadi apabila di suatu wilayah hilal tidak dapat terlihat ketika proses rukyatul hilal atau di suatu wilayah hilal belum wujud bilamana menerapkan konsep wujudul hilal. Beranjak dari permasalahan di atas akan timbul pertanyaan bagaimana konsep wilayatul ḥukmi ini mampu mengakomodir kedua konsep tersebut, di mana wilayah hukum yang masuk didalamnya dalam realitanya belum memenuhi kriteria untuk masuk awal bulan baru. Di sisi lain, penelitian ini juga ingin mengungkap kelebihan dan kekurangan antara konsep rukyatul hilal dan wujudul hilal di era saat ini, dengan harapan mampu memberikan kritik positif dalam membangun kesamaan pandangan demi kemaslahatan umat.Kata Kunci: Rukyatul Hilal, Wujudul Hilal, Wilayatul Ḥukmi